A Complementary Metal‐Displacement Solid‐Phase Extraction Strategy for the Sensitive and Selective Colorimetric Detection of Hg2+. Issue 17 (19th June 2017) - Pathak, Uma; Mathur, Sweta; Pandey, Lokesh Kumar
Abstract: A metal displacement strategy complemented with solid phase extraction has been utilised for selective and sensitive detection of Hg 2+ in pure aqueous medium. Rationally designed Ni 2+ ‐3‐hydroxythioflavone complex as Hg 2+ chromogenic sensing probe was synthesized and immobilized on silica. Visual detection of Hg 2+ at 2 ppb was achieved very conveniently by simple treatment of the Ni 2+ ‐3‐hydroxythioflavone decorated silica with contaminated water without any work up. Visual detection, simple procedure, ease of preparation, stability, selectivity and sensitivity renders this method applicable for detection of Hg 2+ in field condition. Abstract : A complementary metal displacement‐solid phase extraction strategy was developed for sensitive and selective colorimetric detection of Hg 2+ in pure aqueous medium. Rationally designed Ni 2+ ‐3‐hydroxythioflavone complex as a chromogenic sensing probe was immobilised on silica to achieve a very convenient and simple optical detection of Hg 2+ .